Reseña Rethinking Heritage in Precarious Times - Melina Yuln (Cadernos NAUI)
Shepherd, Nick (Ed.). Rethinking Heritage in Precarious Times: Coloniality, Climate Change, and Covid-19 (1st ed.). London: Routledge. 2023, 373 p. https://doi.org/10.4324/9781003188438